Effect of COVID-19 Pandemic on Indian Construction Projects: Reflection on Major Root Cause of Delays and Recommendation to Overcome Current Crises - Rai, Sandeep; Sharma, Anamika (Technium Social Sciences Journal, 2021)
Indian construction sectors play an essential role in economic growth and are the most significant employment generator hub. However, the worldwide spread of the COVID-19 pandemic has caused vast economic slowdown; restrict economic activities, slump global demands. India's construction sector is not unscathed from changing economic impacts. Many findings have revealed that under the ongoing COVID-19 pandemic, India's construction projects are delay due to the migration of laborers and the disrupted supply chain. It is legitimate to determine the most significant factor affecting the performance of construction projects under the COVID-19 pandemic. This study investigates the factor affecting the performance of construction projects in India under the COVID-19 pandemic. A qualitative research method is used to conduct semi-structured interviews with construction industry experts and lawyers to gather information regarding the causes of delays. Data from the interviews highlight the prevailing scenario on the inordinate delays caused in executing construction projects under pandemics. The data analysis identifies that most of the construction projects were affected due to difficulties on operational, financial, and legal issues faced by the project stakeholders under the COVID-19 pandemic. The suitable mitigation measures are suggested based on analyzing data to improve construction performance parameters of construction projects by adopting the latest technology like building information modeling, 3-D printing, and big data to monitor construction projects more effectively. The findings of this study provide insights into the difficulties faced by the construction industries in the pandemic, lay the foundation for future work of academicians, policymakers, construction firms to encourage social-economic transformation and development across India in case of any future pandemic.